Analisis Keberadaan Sistem I-GSW Untuk Perlindungan Menara Transmisi 150 KV Terhadap Sambaran Petir Langsung - Novri Andrean; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The ground wire serves as a protective phase wire from lightning strikes, problems arise when lightning strikes the ground wire. There for the lightning current flows in the ground wire, thus a voltage increase occurs in the tower. The technology that has been developed by ITB and PT. PLN Persero is the I-GSW system functions to protect the transmission tower from lightning currents flowing into the construction of the tower due to lightning strikes directly on the ground wire. In this research the ATP-EMTP software was used as an observation and analysis tool for voltage rises in the tower during a lightning strike immediately before and after the installation of the I-GSW system. The higher the earth grounding resistance value and the higher the lightning current striking so that the I-GSW system the stronger to protect the transmission tower from the increase in voltage The greater the injection of lightning strikes the tower voltage will be greater so that the I-GSW system will protect the tower with a large so that the tower voltage increase using the I-GSW system will not be large because it has been protected by the I-GSW system. The closer the distance of the flash point location on the tower, the higher the tower voltage increase and vice versa the farther the location of the flash point on the tower, the smaller the voltage increase on the tower.Keywords: ATP-EMTP, I-GSW System, Ground Wire, Lightning Current, Ground Type Resistivity